Benefits of modern fishery technology adoption amongst coastal fishermen in West Coast of Malaysia - Mazuki, Raidah (2016)
The purpose of this study was to describe the benefit of modern fishing technology adoption among the coastal fishermen in West Coast of Peninsular Malaysia. Specifically, the objectives for this research were 1) To determine the demographic profile of respondents, 2) To ascertain the level of independent variables (perceived ease of use-PEOU, perceived usefulness-PU, attitude-AT, compatibility-CP and subjective norm-SN) with dependent variable (the benefit of modern fishing technology adoption), 3) To identify the relationship between socio-demographic factors (age-X1, level of education-X2, level of income-X3, fishing experience-X4 and fishermen category-X5) with the benefit of modern fisheries technology adoption among the coastal fishermen community, and 4) to determine the relationship between technology acceptance constructs (perceived ease of use-PEOU, perceived usefulness- PU, attitude-AT, compatibility-CP and subjective norm-SN) and the benefit of modern fisheries technology adoption. This study involved 30 licensed fishermen as respondents in pilot test and a total of 200 respondents to the actual data collection. This study employed a quantitative method using a set of questionnaire that was developed and adopted from previous research instruments. These studies were using a two stage cluster sampling. Respondents for this study are comprised of the coastal fishermen that were registered under Persatuan Nelayan Kawasan (PNK). This study was conducted in four PNK which is PNK Sg. Besar, PNK Melaka Barat, PNK Teluk Kemang and PNK Batu Pahat. The data were analyzed using SPSS. For purposes of analysis, descriptive and inferential analysis was used. Inferential analysis such as the Pearson correlation, Simple Linear Regression analysis also concluded that the only perceived usefulness and compatibility have a significant relationship towards the benefit of modern fishing technology adoption. Chi-square was tested to determine the selected sociodemographic and as a result only the level of income has a positive and significant correlation (χ2 = 29.096), with significance level 0.000 towards the benefit of modern fishing technology adaptation of fishermen on the West Coast, Malaysia. In short, after more than 30 years of fishing technology implementation, coastal fishermen can dispersed the benefit of using the modern fishing technology in their life as one revolution to enhance their socio-economic since the low level of modern fishing technology from this location study. Besides, they have their own commercial body after involved in PNK. Thus, the PNK, fisheries agencies with help of government should keep improve their programme in order to influence the coastal fishermen. It is to hope that the impact of modern fishing technology will be higher towards the coastal fishermen.